GRATIFIKASI KEPADA PEJABAT DALAM TINJAUAN PERSPEKTIF HUKUM ISLAM - Rasyidin Rasyidin (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2017)
In Islam, (Gratification) gift is considered as one way to bring closer brotherhood or friendship. For the person who gives and receives the gift, It is advisable to accept it even if the prize is seemingly despicable and useless. . However, Islam also gives certain signs in the matter of prizes, both with respect to the giver of the gift and the recipient. The bribes are very dangerous for people's lives because they damage the various orders of the existing system in society and cause carelessness and mistakes in the law so that the law can be played with money. Bribing in legal matters is giving something , Either in the form of money or other to the legal officer in order to be free from legal threats or get a light sentence. Such acts are strictly prohibited in Islam and agreed upon by scholars as haram. The property received from the bribe is classified in the treasures obtained through the vanity road. So to keep the benefit of our people avoid the things that we do not want let we realize in accordance with government circular No: SE-02/BL/2010 concerning the prohibition of giving rewards/rewards to (Judges) officials/officials of Bapempam-LK.